Premarket Development Times for Innovative Vaccines––To What Extent Are the Coronavirus Disease 2019 (COVID-19) Vaccines Outliers?. (29th April 2021) - Beall, Reed F; Kesselheim, Aaron S; Hollis, Aidan
Abstract: One reason expressed in surveys of people reporting coronavirus disease 2019 (COVID-19) vaccine hesitancy is how rapidly these vaccines have reached the market. To estimate the length of time the COVID-19 vaccine spent in research and development as compared to other novel vaccines, we apply previously established methods for estimating medical product development times, using the key associated patent filings cited by the manufacturer as the marker of when commercial development activity began. Applying these methods to a cohort of recently approved innovative vaccines and comparing them to the first-approved COVID-19 vaccine (BioNTech/Pfizer), we found key patent filings for the technology in this COVID-19 vaccine occurred 10.0 years prior to regulatory authorization. By this metric, the development timelines for innovative vaccines have been shortening since the 1980s, and the COVID-19 vaccine comfortably fits within this pattern. Vaccine development timelines have now even drawn to parity with many of the most commonly used drugs. Abstract : Despite their perceived speed-to-market, coronavirus disease 2019 (COVID-19) vaccines have had underlying technology in development for many years. There has been a pattern of steadily decreasing development vaccine development times since the 1980s, drawing parity with many commonly used types of drugs.